(untitled) (Namibian Journal for Research, Science and Technology, 2022)
The main aim of this study was to compare the performance of the two National Systems of Innovation for Namibia and Botswana and how they influence national economic development & competitiveness. A mixed method research approach was applied to conduct a comparative analysis of Namibia and Botswana’s National Systems of Innovation for national economic competitiveness. Two phases were adopted, namely, quantitative research through survey questionnaire and qualitative research from generated thematic areas, i.e. characteristics of an effective national system of innovation; Namibia-Botswana Science, Technology and Innovation Policy Framework and Strategies; Science, Technology and Innovation Resources linked to Wealth Creation. It also established the Challenges faced by the two countries in implanting STI Policies & Strategies; Solutions needed to improve STI Policies and Strategies for Namibia and Botswana; the natural endowment for Namibia and Botswana; the role of Governments in improving economic competitiveness Furthermore, the study managed to establish the following key policy recommendation and suggested areas of further research to build an effective and efficient National System of Innovation, which is economically viable and helps build a nation’s competitive advantage.